Corruption and system change in the Czech Republic: Firm-level evidence - Petra Koudelková (DANUBE: Law, Economics and Social Issues Review, 2015)
Corruption is a widespread phenomenon in all countries undergoing market transition. However, the Czech Republic stands apart, with its incredible entanglement of corruption, politics and business. Although corruption on the firm level in the Czech Republic is heavily criticized, the results of our in-depth interviews conducted with Czech SMEs showed that almost every firm has encountered some form of corruption and even used corruption to either increase sales, help negotiations, or increase production. Most of our respondents admitted that corruption was useful for day-to-day business. This article aims to obtain information about the state of corruption in enterprises in the Czech Republic and map the behaviour of entrepreneurs in companies. Our results offer ways to fight corruption: apart from highlighting the negative traits of corruption, emphasis should be made on determining to what extent corruption would be acceptable for firms and their clients. This could be useful for designing various state policies that might influence system change and market development in CEECs and both directly and indirectly influence the volume of corruption.
Keywords: 330; Corruption; Types of Corruption; Firm-level Corruption; Corruption in the Czech Republic; Corruption in Post-communistic Countries